Volume 17: Transportation Systems 2008
DOI: 10.1115/imece2008-68343
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Speed Control System for Vehicle Approaching and Driving on a Curve

Abstract: Based on the curvature information for an upcoming road, an automatic speed control system regulates vehicle speed to improve vehicle curve following performance. The road information is extracted from a digitally stored map using the current vehicle position obtained from Global Positioning System (GPS) data. Then, a safe curve speed is determined using the lateral dynamics of vehicle in turn to ensure proper curve handling. Other factors, such as vehicle characteristics, driver preferences, and road and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Zhang et al [12] concluded that the curve speed was related to the drivers' preferred velocity and the initial velocity on a curved road. Lee et al [13,14] added three different gain factors associated with vehicles, roads and drivers to the curve speed model to represent how these factors affect the curve speed. However, the process of determining the appropriate gain values was carried out without any on-field experiment for further verification.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [12] concluded that the curve speed was related to the drivers' preferred velocity and the initial velocity on a curved road. Lee et al [13,14] added three different gain factors associated with vehicles, roads and drivers to the curve speed model to represent how these factors affect the curve speed. However, the process of determining the appropriate gain values was carried out without any on-field experiment for further verification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The superelevation i y = 0.04 rad and four kinds of common road adhesion coefficients are 0.4 (gravel), 0.6(wet asphalt), 0.8(dry asphalt) and 0.85(dry concrete) [27]. The curve radiuses are 100 200, 400 and 1000 m. Based on these conditions, four existing curve speed models including the simplified model [27], Glaser's model [8,9], Chen's model [10] and Lee's model [13,14] were compared with the proposed model. Fig.…”
Section: Comparisons With Existing Curve Speed Modelsmentioning
confidence: 99%
“…However, speed limits that are specified for an extended zone do not always reflect the appropriate speed on each road segment in that zone, e.g. in curves [GNL07,Lee08]. Additionally, speed limits are usually fixed, while the appropriate speed varies with day/night and weather conditions, i.e.…”
Section: Longitudinal Assistancementioning
confidence: 99%
“…Zhang (Zhang et al, 2012) designed vehicle longitudinal dynamics model using the traction force, aerodynamic force, rolling resistance and road slope. Lee (Lee, 2008) proposed curve speed control system using the upcoming curvature information. The acceleration of vehicle was generated from the current vehicle speed and the desired curve speed.…”
Section: Introductionmentioning
confidence: 99%